What Can Be Changed Through Contact? Possessive Syntax in Megleno-Romanian and Eolian Compared - Sara N. Cardullo; Ștefania Costea (Languages)
This article explores the order of possessives with respect to nouns in Megleno-Romanian, a branch of Daco-Romance, and Eolian, a variety of southern Italo-Romance. Both are in intense language contact situations, the former with the south Slavonic varieties of Bulgarian and Macedonian, the latter with the southern Italo-Romance variety of Sicilian along with southern regional Italian. In particular, we show that while superficially, both Megleno-Romanian and Eolian copied the patterns found in their respective contact languages, the situation is much more complex. Megleno-Romanian shows high noun movement with kinship terms and low noun movement with common nouns, a situation also found in south Slavonic. In the case of Eolian, younger speakers categorically lack N-to-D movement with kinship terms, reflecting the typical Sicilian pattern. In both cases, this gives rise to prenominal possessives, thus diverging from the most common position of possessives in Eastern Romance, which are generally postnominal in unmarked contexts. Ultimately, these case studies show that the position of possessives is epiphenomenal to the level of noun movement in the varieties under investigation. On this note, deeper structural borrowing concerning the nature of possessives (i.e., whether they have an adjectival or determiner value) did not emerge in our findings and is worthy of further investigation.